A STRATEGIC FRAMEWORK FOR UZBEKISTAN’S TRANSITION TO A GREEN ECONOMY: EXAMINING EXISTING OBSTACLES AND PROSPECTIVE OPPORTUNITIES (American Journal of Business Management, Economics and Banking, 2025)
In recent years, the economy of New Uzbekistan has experienced sustained growth. Similar to other emerging economies, this expansion has been driven by intensive resource use and the prioritization of industrial development. However, such elevated production levels have imposed adverse environmental consequences. High pollution levels generate significant economic costs—rising healthcare expenditures, declining labor productivity, and increased rates of premature mortality. Consequently, to mitigate ecological damage, optimize resource allocation, and secure genuine economic advancement, Uzbekistan must transition toward a green economy. Moreover, accurately estimating the respective contributions of capital and labor to national output, assessing how environmental quality affects labor efficiency, and forecasting these indicators are indispensable prerequisites for that transition. This article examines the theoretical foundations of sustainable development, reviews international experience, and identifies the obstacles and opportunities that Uzbekistan faces on its path to a green economy. It also presents a current macroeconomic analysis and a forward-looking microeconomic assessment, based on which econometric models are constructed and their parameters estimated.